PENERAPAN MODEL ASSURE DALAM MEDIA PELATIHAN - Dedi Restendi (Widyadewata, 2021)
Selecting media in a training is essential as an attempt of instructor/widyaiswara to create effective learning process in terms of achieving learning objectives. This study aims to determine the application of ASSURE Model. This study uses quantitative approach involving 55 Widyaiswara at Religious Education and Training Centers throughout Indonesia as samples. Data collection techniques used questionnaires. The data were analyzed descriptively and quantitatively. The results show that widyaiswara in general have applied the model in media selection. It also concludes that during the model application, the instructors were administratively-oriented, but not to the need. Thus, this study recommends to entangle participants' need over the media preference and their willingness to carry out evaluation and continuous revision. Keywords: Widyaiswara; Instructional Media